Value-add application of waste plastic in road pavement construction - Chua, Rachel Min Jing (2019)
Singapore has a small land area with limited resources. As such, it is necessary to encourage waste minimisation and make full use of our natural resources. This study aims to investigate the feasibility of using waste Polypropylene plastic (PP) and Jurong Sedimentary Rocks (JSRs) for low traffic Porous Asphalt Mix (PAM) pavements construction. The success of this project will help to reduce plastic waste and put the excess excavated JSR to good use by substituting granite aggregates in pavements construction. In the preliminary study, 5 experimental groups (G1 to G5) with different composition of granite aggregates were investigated. 4.5% of PG 76 binder was used in this study for batching of specimens and the sedimentary rock aggregates. The experimental groups of different gradation design were analysed through laboratory tests such as Draindown, Permeability, Marshall Stability and Cantabro Abrasion tests to assess the best gradation design, which was found to be G3. In the main study, 3 experimental blends (Blend A to Blend C) of different plastic content are fabrication using the best gradation design determined from the preliminary study i.e. G3. Similarly, the samples were analysed with the same laboratory tests and the Dynamic Creep Test to assess the adequacy of the replacing granite with JSR and portion of the bituminous binder with PP plastic for low- strength pavement. The tests results show that Blend B (5% plastic with JSR) is the optimum plastic content. To conclude, using JSR and PP for low-strength pavement seems to be a viable option. The study has confirmed that by adding PP, it improves the fatigue resistant, improve road strength and decrease porosity. While adding more plastic does helps to improves the fatigue resistant and decrease porosity as it increases from 5% to 10% PP, it does not necessarily improves road strength. It peaks at around 5.4% and starts to decrease.